UPAYA PENINGKATAN HASIL BELAJAR DENGAN MENGGUNAKAN MODEL THINK PAIR SHARE PADA MATERI KEBERAGAMAN SOSIAL, BUDAYA DAN EKONOMI DI MASYARAKAT PADA KELAS VI SDN 26 BILAH HULU - Juraidah Hasibuan (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This research aims (1) to find out whether there is an increase in student learning outcomes in PKN subjects using the Think Pair learning model on Social, Cultural and Economic Diversity in Society in Class VI SDN 26 Bilah Hulu (2) To find out how learning outcomes improve students in PKN subjects whose learning uses the Think Pair Share Model on Social, Cultural and Economic Diversity in Society in Class VI SDN 26 Bilah Hulu. This research is Classroom Action Research. The subjects of this research were Class VI students of SDN 26 Bilah Hulu, Labuhanbatu Regency with 32 students studied, with 18 male students and 14 female students. The object of this research is to improve PKN learning outcomes on social and cultural diversity material in society using the think pair share (TPS) learning model. Based on the research results, it can be concluded that implementing learning using the think pair share model can improve learning outcomes in the PKN subject, social diversity material for Class VI students at SDN 26 Bilah Hulu for the 2022/2023 academic year. From the initial condition to the final condition, there was an increase in learning outcomes from an average of 52.58% in the initial test to 64.52% in cycle I, while in cycle I it was 64.52% to 80.65% in cycle II. In the learning process there is also improvement. In the final condition, students are more active in PKN learning on Social, Cultural and Economic Diversity in Society material. Meanwhile, the initial test learning outcomes reached 41.94%, increasing to 70.97%, while from cycle I it was 70.97%, increasing to 87.10% in cycle II. Observations of learning management and student activities in participating in PKN learning using the think pair share model also experienced an increase, namely in cycle 1 teacher observations reached 67.50% and increased to 87.50% in cycle II, while student observations in cycle I reached 65. 00% increased to 82.50% in cycle II.